2022
DOI: 10.2503/hortj.utd-320
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoid 3',5'-Hydroxylase (<i>F3'5'H</i>) Gene Polymorphisms Co-segregate with Variation in Anthocyanin Composition in the Flower Petals of Lisianthus [<i>Eustoma grandiflorum</i> (Raf.) Shinn.]

Abstract: This study investigated genetic polymorphism related to anthocyanin composition variation in lisianthus (Eustoma grandiflorum) flower petals. Three different bands were detected by genomic polymerase chain reaction using specific primers based on the reported flavonoid 3',5'-hydroxylase (F3'5'H) gene sequence. Our genetic study revealed that they were allelic. They were named F3'5'H1-1, F3'5'H1-2, and f3'5'h1-2. F3'5'H1-1 and F3'5'H1-2 differed in the length of the intron. Allele f3'5'h1-2 possessed a retrotra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Sun et al [57] confirmed that the heterologous expression of PCFH belonging to the CYP75B subfamily could produce a kind of delphinidin derivative (3′,5′-hydroxylated anthocyanidins) in vivo and its encoded protein had the 3′,5′-hydroxylation function. Takatori et al [62] found that F3′5′H genes were involved in the synthesis of delphinium in Eustoma grandiflorum (Raf.) Shinn, and of other types of anthocyanins, such as cyanidin-type anthocyanin and pelargonidin-type anthocyanin that produce various flower colors.…”
Section: Functional Analysis Of Blueberry F3′5′hmentioning
confidence: 99%
“…Sun et al [57] confirmed that the heterologous expression of PCFH belonging to the CYP75B subfamily could produce a kind of delphinidin derivative (3′,5′-hydroxylated anthocyanidins) in vivo and its encoded protein had the 3′,5′-hydroxylation function. Takatori et al [62] found that F3′5′H genes were involved in the synthesis of delphinium in Eustoma grandiflorum (Raf.) Shinn, and of other types of anthocyanins, such as cyanidin-type anthocyanin and pelargonidin-type anthocyanin that produce various flower colors.…”
Section: Functional Analysis Of Blueberry F3′5′hmentioning
confidence: 99%